Immediate and Delayed Mortality of Four Stored-Product Pests on Concrete Surfaces Treated with Chlorantraniliprole - Nickolas G. Kavallieratos; Maria C. Boukouvala; Erifili P. Nika; Nikoleta Eleftheriadou; Dimitrios N. Avtzis (Insects, 2021)
Chlorantraniliprole is an effective pesticide against a plethora of pests, but its efficacy against stored-product pests is very poorly explored. In this study we treated concrete surfaces with four different doses of chlorantraniliprole (0.01, 0.05, 0.1, and 0.5 mg a.i./cm2) against the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) adults and larvae, the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) adults, the rice weevil, Sitophilus oryzae (L.) (Coleoptera: Curculionidae) adults, and the flour mite, Acarus siro L. (Sarcoptiformes: Acaridae) adults and nymphs, to examine the immediate mortalities after 1, 2, 3, 4, and 5 days of exposure. Additionally, the delayed mortality of the individuals that survived the 5-day exposure was also evaluated after a further 7 days on untreated concrete surfaces. We documented high mortality rates for all tested species and their developmental stages. After 5 days of exposure to 0.5 mg a.i./cm2, T. castaneum larvae and A. siro adults exhibited the highest immediate mortality levels, reaching 96.7% and 92.2%, respectively. Delayed mortality was also very high for all tested species and their developmental stages. Nymphs of A. siro displayed a 96.3% delayed mortality followed by the adults of R. dominica (98.6%) after exposure to 0.5 mg a.i./cm2. All other tested species and their developmental stages reached complete (100.0%) delayed mortality, where even 0.01 mg a.i./cm2 caused ≥86.6% delayed mortality in all species and their developmental stages. Taking into consideration the effectiveness of chlorantraniliprole on this wide range of noxious arthropods, coupled with its low toxicity towards beneficial arthropods and mammals, this pesticide could provide an effective management tool for stored-product pests in storage facilities.